2019
DOI: 10.21776/ub.majalahkesehatan.006.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Kadar Interleukin-4 Dan Interleukin-8 Feses Neonatus Prematur Yang Mendapat Asi, Predominan Asi, Predominan Susu Formula, Dan Susu Formula

Abstract: Bayi prematur apabila usia gestasi kurang dari 37 minggu saat lahir. Strategi yang telah terbukti untuk mengurangi kejadian risiko infeksi,dan gangguan saluran pencernaan pada bayi prematur adalah konsumsi air susu ibu (ASI). Saluran cerna dipengaruhi proses regulasi sitokin proinflamasi dan antiflamasi. Hasil penelitian menunjukkan interleukin-4 dan interleukin-8 berperan pada kondisi inflamasi saluran cerna. Penelitian ini untuk membuktikan adanya perbedaan kadar interleukin 4 (IL-4) dan interleukin 8 (IL-8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Preterm neonates accompanied by inflammation will cause increase systemic IL-4 levels. 18 Benkoe et al who evaluated 11 cytokines in premature infants with Necrotizing Enterocolitis found IL-4 was 1.4 times lower than the control group, while IL 6, IL 8 and IL 10 (inflammatory cytokines) increased. 19 In Lusyati et al study regarding levels 25 cytokines in the first 7 days of neonatal life ≥ 24-72 hours of age with a median value of 3 (1-5.5) pg/ml.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Preterm neonates accompanied by inflammation will cause increase systemic IL-4 levels. 18 Benkoe et al who evaluated 11 cytokines in premature infants with Necrotizing Enterocolitis found IL-4 was 1.4 times lower than the control group, while IL 6, IL 8 and IL 10 (inflammatory cytokines) increased. 19 In Lusyati et al study regarding levels 25 cytokines in the first 7 days of neonatal life ≥ 24-72 hours of age with a median value of 3 (1-5.5) pg/ml.…”
Section: Discussionmentioning
confidence: 98%
“…Low levels of IL-4 will be found in patients with necrotizing enterocolitis. 18 Interleukin-4 is one of the antiinflammatory cytokines that can prevent inflammation. Neonates who have an IL-4 Z score of less than -1 have the possibility for the development of neuronal disorders.…”
Section: Discussionmentioning
confidence: 99%